Adding Interactive Graphic Organizers to a Whole-Class Slideshow Lesson - Lopez-Villarroel, M; Ponce-Arias, H; Loyola-Fuentes, M (Springer Netherlands, 2018)
This study examines the effects of including interactive graphic organizers into a whole-class PowerPoint lesson as an instructional approach intended to improve student engagement and generative learning in schools. A software application was developed and integrated into PowerPoint that makes it possible for the instructor to fill in empty graphic organizers during PowerPoint projection mode. The participants were 152 fourth-grade students selected from three schools that were grouped in four classrooms. Each classroom was divided in two groups—graphic organizer and content-based. The graphic organizer group was taught using an 11-slide PowerPoint presentation on a social study topic that included two empty graphic organizers plus two additional slides explaining how to make a comparison. The content-based group was taught using the same presentation but without these additional slides plus a set of questions students had to answer as a class activity. The lessons were recorded and the verbal statements between instructor and students examined using the Flanders Interaction Analysis System. Results indicated significant differences in how instructors and students interacted in each group, including more questions asked by teachers (d = 1.99) and more students participating in the classroom discussion in the graphic organizer group (d = 1.76). Learning outcomes showed that the graphic organizer group outperformed the content-based group on a memory test (d =.45) and a comprehension test (d =.44). These results encourage the use of graphic organizers as an instructional approach, and are consistent with a generative theory of learning. © 2018, Springer Nature B.V.